(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
This Research Aims To Shed Light On The Importance Of Entrepreneurship Education In Higher Education And Its Role In The Consolidation Of A Entrepreneurial Culture For University Student, Which Qualify Him To Be A Successful Element In Practical Life, Imaginative Contributions To The Study Of Concepts Of Entrepreneurship Education And The Importance Its And Objectives To The Recall And Evolution, Then We Add The Reality Of Entrepreneurship Education In The Arab World, And Algeria Exactly, And We Have Incorporated The Most Important Global Experiences In Entrepreneurship Education. Keywords - Entrepreneurship, Entrepreneurship Education-Entrepreneurial Culture-University.